2011
DOI: 10.1124/jpet.111.181834
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Receptor Type 3 Antagonists Improve Obesity-Associated Fatty Liver Disease in Mice

Abstract: Obesity is a major cause for nonalcoholic fatty liver disease (NAFLD). Previous studies suggested that alterations in intestinal motility and permeability contribute to the development of NAFLD. Serotonin and serotonin receptor type 3 (5-HT 3 R) are key factors in the regulation of intestinal motility and permeability. Therefore, we studied the effect of the 5-HT 3 R antagonists tropisetron and palonosetron on the development of NA-FLD in leptin-deficient obese mice. Four-week-old ob/ob mice and lean controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 32 publications
3
58
1
1
Order By: Relevance
“…5-HT, which is produced at high amounts in the GI tract, is involved in the regulation of intestinal motility and possibly permeability [7,17,29]. Hence, we quantified 5-HT concentration, TPH1 mRNA expression, as well as 5-HT transporter (SERT), and 5-HT 3A R protein content in the duodenum of mice (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5-HT, which is produced at high amounts in the GI tract, is involved in the regulation of intestinal motility and possibly permeability [7,17,29]. Hence, we quantified 5-HT concentration, TPH1 mRNA expression, as well as 5-HT transporter (SERT), and 5-HT 3A R protein content in the duodenum of mice (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Protein was prepared and antibodies were applied as described earlier [17]. Semi-quantitative real-time PCR analyses were performed using SsoFast EvaGreen Supermix (BioRad Laboratories, Munich, Germany) and were carried out in an iCycler (BioRad Laboratories, Munich, Germany) with 40 cycles of a two-step PCR (denaturation 95°C for 35 s, denaturation 95°C for 5 s, annealing/extension 62°C for 10 s).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides this, Haub et al have suggested that serotonin may raise the fat concentration of the liver [29]. Comparing lean control mice, there is an increase of duodenal Htr3a protein expression and plasma serotonin levels in ob/ob mice.…”
Section: Serotonin and Lipid In The Liver And The Circulationmentioning
confidence: 97%